Principles of Geotechnical Engineering, 9th Edition - Braja M. Das; Khaled Sobhan (Cengage Learning, 2017)
Readers gain a valuable overview of soil properties and mechanics together with coverage of field practices and basic engineering procedures with Das and Sobhan's PRINCIPLES OF GEOTECHNICAL ENGINEERING, 9E. This introduction to geotechnical engineering forms an important foundation for future civil engineers. This book provides critical background knowledge readers need to support any advanced study in design as well as to prepare them for professional practice. The authors ensure a practical and application-oriented approach to the subject by incorporating a wealth of comprehensive discussions and detailed explanations. Readers find more figures and worked-out problems than any other book for the course to ensure understanding. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.